Continued rise in forceps delivery in a university hospital over a 6-year period: is this trend acceptable. (16th November 2010) - Umranikar, A; Campbell, L; Rogers, J; Brackley, K
Abstract : Introduction: Southampton University Hospital (SUHT) has maintained a relatively low Caesarean section (CS) rate over the past 6 years, despite being a tertiary referral centre. However an increase in forceps delivery has been observed raising concerns over perineal trauma risks. Design: A review of computerised obstetric data from 2003 to 2009 in a large university hospital and comparison with maternity statistics for England. Results: Our CS rate has remained consistently lower (21–22%) and instrumental deliveries higher than England. The lower CS rate is mainly due to elective cases which have shown a decline to 6.7%, in contrast to a gradually rising national rate for both elective (9–10%) and emergency CS (15%). The rates of normal births are comparable, decreasing nationally and locally (from 65% to 61%). There has been a sharp rise in the instrumental delivery rate at SUHT since 2006 from 12% to 16%, mostly attributable to increased forceps (12%) with a simultaneous fall in ventouse (3.8%). This is mainly due to an increase in non-rotational forceps in nulliparous women for failure to progress. The rate of inductions (20–21%) and use of epidural analgesia (20–21%) have been stable at Southampton University Hospital Trust since 2006. The rising rate of instrumental deliveries has not resulted in a reduction in emergency second stage CS, which remains steady at 6–7%. Conclusion: Our increasing trend in forceps deliveries is not reducing second stage CS but may be avoiding the rise in emergency CS seen nationally. Our lower ventouse rate compared to forceps is particularly apparent.